INOVASI PEMBELAJARAN MELALUI FLIP BOOK “DUNIA KITA” UNTUK MENINGKATKAN LITERASI PESERTA DIDIK KELAS III SD NEGERI KRAPYAK WETAN - Anisa Salsabila; Arip Febrianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop a digital learning medium in the form of an interactive flip book titled “Dunia-Kita”, designed to improve the literacy of third-grade elementary students in the subject of Natural and Social Sciences (IPAS). The research used a Research and Development (R&D) method with the ADDIE model, consisting of analysis, design, development, implementation, and evaluation phases. The study involved 10 students in a limited trial and 20 students in a field trial. Data were collected through observation, questionnaires, and tests. Validation results showed the media scored 92% from a media expert and 98% from a content expert, both categorized as “very feasible.” Practicality was measured with teacher responses scoring 88% and student responses 91%, indicating the media is “very practical.” Effectiveness was measured using pretest and posttest. In the limited trial, scores increased from 57.7% to 86.4% (a 28.7% improvement), and in the field trial from 55.1% to 93% (a 37.9% improvement). These results indicate a significant increase in student literacy. In conclusion, the “Dunia-Kita” flip book is considered feasible, practical, and effective for enhancing literacy in IPAS learning for third-grade students.